Plastic capacity of bolted RHS flange-plate joints under axial tension. Issue 3 (2nd July 2016) - Mudrov, Andrej; Šaučiuvėnas, Gintas; Sapalas, Antanas; Talvik, Ivar
Abstract: This article considers the calculation of load-bearing capacity of flange-plate joints with bolts along two sides of rectangular hollow sections (RHS) under axial tension. It provides a review and comparison of various calculation methodologies for establishing the load-bearing capacity of RHS flange-plate joints, such as suggested in EN 1993-1-8:2005 and STR 2.05.08:2005 as well as those proposed in different countries and by other authors. Common design principles and derived results for load-bearing capacity of flange-plate joints have been analysed and compared. Following the numerical modelling, which has been done using ANSYS Workbench finite element program, the derived results for load-bearing capacity have been compared with analytical load-bearing capacity results for flange-plate joints of the same structure. The analysis has focused on one type of flange-plate joints with bolts – both preloaded and non-preloaded – along two opposite sides of the tube, with the flange thickness of 15 mm and 25 mm.